Kinetic and thermodynamic parameters of nisin thermoinactivation. (September 2020) - Moretti de Almeida, Gabriel; Nóbrega Mendonça, Carlos Miguel; Converti, Attilio; Pinheiro de Souza Oliveira, Ricardo
Abstract: Understanding the thermal inactivation of biopreservatives in food matrixes is essential for their proper use in the food industry, enabling reduction of heating time and optimization of heating temperature. With this aim in mind, the effect of heat treatment on the activity and thermostability of commercial nisin from Lactococcus lactis was investigated. Residual activity tests performed for 90 min in the 70–86 °C temperature range at pH 3.0 demonstrated that bacteriocin thermoinactivation followed first-order kinetics. Low values of the inactivation rate constant (0.0089–0.0892 min −1 ) and high values of the decimal reduction time (25.8 ≤ D -value ≤ 258.4 min) indicated excellent nisin thermostability in the lower end of the investigated temperature range, but the thermal resistance constant ( z -value) was only 15.4 °C, which pointed out poor thermoresistance at the higher end. Thermodynamic parameters estimated for nisin irreversible thermal inactivation were energy, enthalpy and Gibbs free energy of activation of 155.1, 152.2–152.3 and 83.5–86.6 kJ mol −1, respectively, and activation entropy of 188.6–192.5 J mol −1 K −1 . If on the one hand these results taken together confirm the thermostability of nisin as a biopreservative in use in the food industry, on the other hand suggest the importance of looking for new more thermostable antimicrobials to use in operations at higher temperatures. Highlights: Kinetic and thermodynamic parameters of nisin thermoinactivation were estimated. Thermal inactivation of nisin was shown to follow first order kinetics. Low values of the inactivation rate constant confirm excellent nisin thermostability. z -Value and activation Gibbs free energy were 15.4 °C and 83–86 kJ mol −1, respectively.